Perkembangan Tren Penelitian Kualitas Pelayanan Di Indonesia - Umar Reza Saputra; Endang Larasati; Tri Yuniningsih; Retno Sunu Astuti (Mahesa Research Center, 2021)
This study aims to be able to provide an overview related to the development of research on service quality in Indonesia taken by the accredited journal Sinta 2 in Indonesia and provide an overview of concepts that are often used by researchers in Indonesia so that they can bring up novelty or development of various service quality research. The sample used is an article on service quality from 2007 to 2020 which discusses service quality. The method in this study, charting the field, is a search technique for classifying articles with established criteria, namely based on research methods, research content (research variables), research sectors used by researchers in Indonesia. The findings obtained were 167 articles contained in 29 accredited journals of Sinta 2 in Indonesia that had met the criteria. Then the articles are classified based on the research method, research content (research variables) and research sector. The conclusion of this research is that the research method used is dominated by quantitative methods. The independent variable used by the researcher is dominated by service quality. The dependent variable is dominated by customer satisfaction. The journal that dominates research on service quality is the Journal of Management Applications. Research on the quality of service in Indonesia is mostly conducted in the private sector